The Effect of Habitus and Work Attitude on Low Back Pain Complaints of Manual Handling Workers or Porters in Benjaran Market Tegal (Public Health Perspective Journal, 2021)
Low Back Pain is an acute pain in the fifth lumbar area and saclaris (L5-S1). It is a musculoskeletal disorder that usually caused by various musculoskeletal diseases, psychological disorders, and incorrect mobilization. There are still high cases of Low Back Pain in Tegal, mainly suffered by the manual handling workers or porters. This study has purpose to analyze the effect of Habitus and Work Attitude on the complaints of Low Back Pain. The type of this study was an analytic survey research conducted by using a cross sectional design. The population used in this study was the manual handling workers or porters in Benjaran Market, Tegal. The sampling was done using an accidental sampling technique. Then, the analysis was done using Bivariate analysis of chi-square and multivariate analysis with multiple linear regressions. The results of analysis using 57 respondents showed that there is an effect of Habitus and Work Attitudes on Low Back Pain complaints of manual handling workers or porters in Benjaran Market, Tegal. Based on the results of this study, it is suggested to periodically check the health condition of the manual handling workers or porters and take precautions that are necessary to do muscle activity before doing the physical activity, and it is recommended to do exercise in 30 or 45 minutes, 3 or 5 times a week.